DIGITAL SERVICE ECONOMY: CURRENT TRENDS AND LABOUR MARKET EFFECTS - Afanasievna Lapina, Marina; Alexandrovich Shirokovskikh, Sergey; Vernikov; Nikolaevna Sepiashvili, Ekaterina (Revista Inclusiones, 2020)
The development of the information society fosters the evolution of an information-driven economic system, the digital economy, which is characterised by active use of information and communication technology and the Internet. Digitalisation brings cardinal change to business landscapes, business processes (both core and non-core), and requirements to and patterns of works or services and exerts significant influence on labour market transformations. The paper outlines scholarly interpretations of the notion of the digital economy and analyses the theory of the post-industrial society in the context of the development of the digital service economy. An expert survey is conducted to identify major structural shifts in the global labour market and map the trends and outlook of digital employment in the digital service economy.